Factors that Influence the Purchase Intention of Luxury Fashion - Mulia, Dipa; Salsabila Asyifa (Dinasti International Journal of Digital Business Management, 2024)
Abstract: Sales of luxury fashion are growing rapidly in Indonesia. Competition from well-known brands is tight, so a separate strategy is needed to build interest in buying this luxury fashion. Consumer behavior in buying luxury goods has its uniqueness, the same thing also happens in interest in purchasing luxury fashion. Consumer purchase intention is influenced by emotional and rational aspects. The main purpose of this research is to formulate the strategy to develop costumer purchase intention of luxury fashion. This research conveys the influence of emotional aspects, namely the influence of brands, experiences, and hedonic behavior, and the influence of rational aspects which include product quality, price, and information, in influencing consumer buying interest in luxury fashion. The research is a quantitative study involving 125 consumers with the criteria of having purchased luxury fashion. The research results show that hedonic behavior, price, and information do not significantly influence consumer buying interest, while product quality, experience, and brand significantly influence consumer buying interest.